City and State in the Medieval Low Countries - Braekevelt, Jonas; Buylaert, Frederik; Dumolyn, Jan; Haemers, Jelle; Keymeulen, Sarah; Lambert, Bart; Lecuppre-Desjardin, Elodie; Lowagie, Hannes; Pajic, Milan; Papin, Kristof; Van Bruaene, Anne-Laure; Van Gassen, Tineke; et al. (Brepols, 2021)
The oeuvre of Marc Boone (Ghent, 1955) has become standard reading for specialists of medieval European towns and cities, as well as for those interested in the history of state building - most notably that of the Burgundian polity. Honoring Ghent University’s venerable tradition of medieval studies begun by Henri Pirenne and building upon the work of his <span class=